Autonomy, Experience, and Reflection. On a Neglected Aspect of Personal Autonomy - Blöser, Claudia (Ethical theory and moral practice, 2010)
The aim of this paper is to suggest that a necessary condition of autonomy has not been sufficiently recognized in the literature: the capacity to critically reflect on one’s practical attitudes (desires, preferences, values, etc.) in the light of new experiences. It will be argued that most prominent accounts of autonomy—ahistorical as well as history-sensitive—have either altogether failed to recognize this condition or at least failed to give an explicit account of it.